Fundamentals of materials for energy and environmental sustainability - Ginley, D. S. (David S.); Kahen, David (Cambridge : Cambridge University Press, 2012)
'How will we meet rising energy demands? What are our options? Are there viable long-term solutions for the future? Learn the fundamental physical, chemical and materials science at the heart of: [bullet] Renewable/non-renewable energy sources [bullet] Future transportation systems [bullet] Energy efficiency [bullet] Energy storage Whether you are a student taking an energy course or a newcomer to the field, this book will help you understand critical relationships between the environment, energy and sustainability. Leading experts provide comprehensive coverage of each topic, bringing together diverse subject matter by integrating theory with engaging insights. Each chapter includes helpful features to aid understanding, including a historical overview to provide context, suggested further reading and questions for discussion. Every subject is beautifully illustrated and brought to life with full color images and color-coded sections for easy browsing, making this a complete educational package. Fundamentals of Materials for Energy and Environmental Sustainability will enable today's scientists and educate future generations'--Provided by publisher.
Machine generated contents note: Preface; Part I. Energy and the Environment: The Landscape: 1. A primer on climate change; 2. Global energy landscape and energy security; 3. Sustainability and energy conversions; 4. Energy cost of materials: materials for thin-film photovoltaics as an example; 5. Economics of materials; 6. Global energy flows; 7. Global materials flows; 8. Carbon dioxide capture and sequestration in deep geological formations; Part II. Non-renewable Energy Sources: 9. Petroleum and natural gas; 10. Advancing coal conversion technologies: materials challenges; 11. Oil shale and tar sand; 12. Unconventional energy sources: gas hydrates; 13. Nuclear energy: current and future schemes; 14. Nuclear nonproliferation; 15. Nuclear waste management and disposal; 16. Material requirements for controlled nuclear fusion; Part III. Renewable Energy Sources: 17. Solar energy overview; 18. Direct solar energy conversion with photovoltaic devices; 19. Materials science and technology: new approaches to high efficiency photovoltaic conversion; 20. Concentrating and multijunction photovoltaics; 21. Concentrating solar thermal power; 22. Solar thermoelectrics: direct solar thermal energy conversion; 23. Off-grid solar in the developing world; 24. Principles of photosynthesis; 25. Harnessing microbial metabolism for biofuels and biomaterials; 26. Aqueous processing of cellulosic biomass for biological and chemical conversion to ethanol and other fuels; 27. Artificial photosynthesis for solar energy conversion; 28. Engineered natural photosynthesis; 29. Geothermal and ocean energy; 30. Wind energy; Part IV. Transportation: 31. Road transportation vehicles; 32. Transportation: aviation; 33. Future of shipping; 34. Fully autonomous vehicles: a far-reaching perspective on potential materials and design implications; Part V. Energy Efficiency: 35. Lighting/appliances; 36. Increasing building energy efficiency through advances in materials; 37. Insulation science; 38. Industrial energy efficiency; 39. Green processing: catalysis; 40. Material availability and recycling: identifying risks and evaluating responses; 41. Life-cycle assessment (LCA); Part VI. Energy Storage and the Role of High Penetration Renewables and Grid Stabilization: 42. Toward stronger, smarter, and more secure electric power grids: advances and challenges in distributed sensing, modeling, simulation, and control; 43. Consequences of high penetration renewables; 44. Materials challenges facing electrochemical energy storage: batteries and capacitors; 45. Mechanical energy storage: pumped hydro, CAES, flywheels; 46. Polymer electrolyte membrane (PEM) fuel cells; 47. Solar fuels; 48. Solar thermal routes to fuel; 49. Photoelectrochemistry; 50. Summary; Appendix A: thermodynamics; Appendix B: electrochemistry.
Includes index.
Keywords: Energy conservation -- Equipment and supplies; Renewable energy sources; Power resources; Fuel; Sustainable engineering -- Materials